Coatings containing finely divided polymers as matting agents.

Micronized polymers are used as alternative matte agents in coatings to address the issues of traditional silica-based coatings, achieving improved scratch resistance, reduced viscosity, and enhanced matte finish performance.

JP7669289B2Active Publication Date: 2025-04-28ソルスティス アドバンスト マテリアルズ ユーエス インコーポレイティッド
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021568475
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-13
Filing Date
2020-05-15
Publication Date
2025-04-28
Estimated Expiration
2040-05-15

AI Technical Summary

Technical Problem

Traditional coatings using precipitated or gel silica as matte agents exhibit undesirable properties such as burning, poor scratch resistance, high binder demand, and increased viscosity, making it necessary to find an alternative matte agent.

Method used

The use of micronized polymers as matte agents in coatings, replacing or partially replacing silica, to achieve a matte finish while improving physical properties and reducing costs.

Benefits of technology

Micronized polymers effectively reduce gloss, enhance scratch resistance, and lower viscosity, resulting in improved coating performance and reduced adverse effects such as burnishing and precipitation during storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669289000001
    Figure 0007669289000001
  • Figure 0007669289000002
    Figure 0007669289000002
  • Figure 0007669289000003
    Figure 0007669289000003
Patent Text Reader

Abstract

A matte finish coating for application to a substrate includes a coating material and a micronized polymeric matting agent in a mixture, the matte finish coating including the micronized polymeric matting agent in an amount of about 0.5% to about 15% of the total weight of the matte finish coating.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates generally to the field of commercial coatings, such as, but not limited to, clearcoats, paints, and inks, among others. More specifically, the present disclosure relates to such coatings that contain finely divided polymers as matting agents. [Background technology]

[0002] Coatings are versatile and have a wide range of applications as commercial and industrial protective coatings, decorative coatings for walls, floors, and other surfaces, paints, inks, and other applications. The substrates on which these coatings can be applied also vary widely, including metal, plastic, wood, film, and paper, among others. In certain applications, it is desirable to control the light reflectance from the surface of the cured coating film. Matting agents are typically added to coatings to obtain a desired low level of gloss and shine. However, matting agents have a significant effect on both the cost of the coating and the physical properties of the coating, so the selection of matting agents must be made carefully.

[0003] Precipitated silica or gel silica has been used as a matting agent in the past. However, precipitated silica or gel silica has been shown to have some undesirable properties when used as a matting agent. For example, such coatings may exhibit burnishing, poor mar, friction, wear, and scratch resistance, poor surface slip and feel, efficiency loss when the coating is stored for a long period of time, settling during storage, friability, high binder demand, and viscosity increase. Therefore, it would be desirable to either partially or completely replace silica in the coating with an alternative matting agent that does not exhibit the problems and shortcomings mentioned above. Furthermore, other desirable features and characteristics of the present disclosure will become apparent from the following detailed description and the appended claims, taken together with the accompanying drawings, summary of the invention, technical field, and background of the present disclosure. Summary of the Invention

[0004] According to one exemplary embodiment, a matte finish coating for application to a substrate is disclosed that includes a mixture of a coating material and a finely divided polymeric matting agent. The matte finish coating includes the finely divided polymeric matting agent in an amount of about 0.5% to about 15% of the total weight of the matte finish coating.

[0005] This Summary is provided to explain select concepts in a concise form that are further described in the Detailed Description, with various embodiments incorporating the concepts described in the Summary. This Summary is not intended to identify key or essential features of the presently disclosed subject matter by reference to the claims or otherwise, nor is this Summary intended to be used as an aid in determining the full scope of the disclosed subject matter, which is properly determined by reference to various embodiments of the present disclosure. [Brief description of the drawings]

[0006] A more complete understanding of the present disclosure may be derived from the accompanying drawings, in which like reference numbers indicate like elements, and in which:

[0007] [Figure 1A] 1 is a graph showing gloss test results for clearcoat compositions at 60 degrees. [Figure 1B] Shown is the same test at 85 degrees. The matting agent loading was 2%.

[0008] [Figure 2A] 1 is a graph showing gloss test results for clearcoat compositions at 60 degrees. [Figure 2B] Shown is the same test at 85 degrees. The matting agent loading was 6%.

[0009] [Figure 3A] 1 is a photograph showing the results of abrasion testing on a clearcoat composition using a 2% matting agent loading. [Figure 3B]The same test is shown at 6% loading.

[0010] [Figure 4A] 1 is a graph showing the viscosity of various coating compositions containing a silica matting agent compared to a finely divided polymeric matting agent. [Figure 4B] 1 is a graph showing the viscosity of various coating compositions containing a silica matting agent compared to a finely divided polymeric matting agent. [Figure 4C] 1 is a graph showing the viscosity of various coating compositions containing a silica matting agent compared to a finely divided polymeric matting agent. [Figure 4D] 1 is a graph showing the viscosity of various coating compositions containing a silica matting agent compared to a finely divided polymeric matting agent.

[0011] [Figure 5A] 1 is a graph showing the results of burnishing tests on various coating compositions at gloss angles of 20, 60, and 85 degrees with a matting agent loading of 5% or 8%. [Figure 5B] 1 is a graph showing the results of burnishing tests on various coating compositions at gloss angles of 20, 60, and 85 degrees with a matting agent loading of 5% or 8%. [Figure 5C] 1 is a graph showing the results of burnishing tests on various coating compositions at gloss angles of 20, 60, and 85 degrees with a matting agent loading of 5% or 8%. [Figure 5D] 1 is a graph showing the results of burnishing tests on various coating compositions at gloss angles of 20, 60, and 85 degrees with a matting agent loading of 5% or 8%.

[0012] [Figure 6A] 1 is a graph showing the results of matte efficiency testing for various coating compositions at gloss angles of 20, 60, and 85 degrees. [Figure 6B]1 is a graph showing the results of matte efficiency testing for various coating compositions at gloss angles of 20, 60, and 85 degrees. [Figure 6C] 1 is a graph showing the results of matte efficiency testing for various coating compositions at gloss angles of 20, 60, and 85 degrees. [Figure 6D] 1 is a graph showing the results of matte efficiency testing for various coating compositions at gloss angles of 20, 60, and 85 degrees. [Figure 6E] 1 is a graph showing the results of matte efficiency testing for various coating compositions at gloss angles of 20, 60, and 85 degrees.

[0013] [Figure 7A] Photographs showing the results of color transfer and scrub resistance tests for paint and ink compositions using 5% matting agent loading. [Figure 7B] Photographs showing the results of color transfer and scrub resistance tests for paint and ink compositions using 5% matting agent loading. [Figure 7C] Photographs showing the results of color transfer and scrub resistance tests for paint and ink compositions using 5% matting agent loading.

[0014] [Figure 8] 1 is a graph showing gloss reduction for various particle sizes of oxidized polyethylene micronized polymers after 5% polymer addition to a control coating.

[0015] [Figure 9] 1 is a graph showing the burnish resistance of oxidized polyethylene micronized polymers of various particle sizes after 5% polymer loading to a control coating.

[0016] [Figure 10] 1 is a graph showing the abrasion resistance of oxidized polyethylene micronized polymer of various particle sizes after 5% polymer loading to a control coating.

[0017] [Figure 11] 1 is a graph showing the viscosity increase of oxidized polyethylene micronized polymers of various particle sizes after the addition of 5% polymer to a control coating.

[0018] [Figure 12A] 1 is a graph showing gloss reduction for polyethylene, polyethylene oxidized, and polypropylene micronized polymers of various particle sizes after 5% polymer addition to control coatings (acrylic and polyurethane coatings, respectively). [Figure 12B] 1 is a graph showing gloss reduction for polyethylene, polyethylene oxidized, and polypropylene micronized polymers of various particle sizes after 5% polymer addition to control coatings (acrylic and polyurethane coatings, respectively).

[0019] [Figure 13] 1 is a graph showing the burnish resistance of polyethylene, polyethylene oxidized, and polypropylene micronized polymers of various particle sizes after 5% polymer loading to a control coating.

[0020] [Figure 14] 1 is a graph showing the abrasion resistance of polyethylene, polyethylene oxidized, and polypropylene micronized polymers of various particle sizes after 5% polymer loading to a control coating.

[0021] [Figure 15] 1 is a graph showing the viscosity increase of polyethylene, polyethylene oxide, and polypropylene micronized polymers of various particle sizes after adding 5% polymer to a control coating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present disclosure provides exemplary embodiments of compositions and methods that include the use of finely divided polymers to partially or completely replace silica as a matting agent for coatings. As used herein, the term "exemplary" means "to serve as an example, instance, or illustration." Thus, any coating composition or method embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. All of the embodiments described herein are exemplary embodiments provided to enable one skilled in the art to make or use the invention, and do not limit the scope of the invention, which is defined by the claims. Coating Composition

[0023] As used herein, the term "coating" or "coating composition" applies broadly to any liquid material that is applied to a solid substrate to form a film on the substrate after drying and / or curing. Thus, as used herein, "coating" can take the form of a variety of compositions used in a variety of industries, such as protective coatings, decorative coatings, paints, inks, etc.

[0024] Coatings generally include one or more film-forming binders and one or more liquid carriers. Coatings may also include 100% solid paint systems and powder coatings. Coatings generally have a film-forming binder content of about 5-100% by weight, and correspondingly about 0-95% by weight of the liquid carrier. The binder generally includes all film-forming components that contribute to the solid portion of the cured composition. Generally, catalysts, pigments, and non-polymeric chemical additives, such as stabilizers described below, are not considered part of the binder solids. Non-binder solids other than pigments usually do not amount to more than about 5-15% of the composition. Suitable film-forming binders may include, for example, polyurethanes, polyesters, polyethylene glycols, polypropylene glycols, polytrimethylene ether glycols, linear and / or branched acrylics and acrylic polyols, acrylic latexes, water-based latexes, acrylic microgels, water-based microgels, or combinations thereof. Generally, the solvent may be any organic solvent and / or water.

[0025] Depending on the type of coating and intended function, one or more additives may be optionally included with the binder and liquid carrier.Suitable additives may include, for example, pigments, rheology control agents, UV absorbers, light stabilizers, catalysts, defoamers, or combinations thereof.Pigments suitable for use are well known in the art and may include, for example, carbon black, titanium dioxide, iron oxide, silicon dioxide, zinc phosphate, barium sulfate, azo pigments, phthalocyanine pigments, quinacridone pigments, pyrrolopyrrole pigments, perylene pigments, pearlescent pigments, metal oxide-coated metal pigments, titanium dioxide-coated aluminum, coated mica or pearl flakes, titanium dioxide-coated mica, graphite effect pigments, platey iron oxides, platey copper phthalocyanine pigments, or combinations thereof.

[0026] Some non-limiting examples of coatings exemplified as inks are provided herein. Gravure ink: Gravure is the primary commercial printing process that can be used to print on substrates such as paper, plastic films, etc. Text and images can be printed. Gravure is an intaglio process in which ink is transferred to paper as droplets from very small cells recessed into the printing surface (e.g., a cylinder or plate). The ink droplets flow and spread together selectively to print the text or image. If the surface tension of the ink droplets is too high, the ink will not spread instantly or sufficiently, and the print will appear rough and grainy. Gravure is distinguished from other processes such as letterpress and lithography. Gravure inks are highly fluid, solvent or co-solvent based inks that dry by evaporation leaving a film of resin and pigment on the substrate. Representative solvents and co-solvents include toluene, xylene, alcohol, acetone, aliphatic hydrocarbons, water, etc.

[0027] Flexographic ink: Flexographic inks generally contain pigments and binder resins dispersed in water. The binder acts as a carrier for the pigment and adheres it to the surface being printed. A wide variety of binder systems have been used in flexographic ink compositions, including acrylic and methacrylic polymers and copolymers, rosin-modified phenolic resins, polystyrene resins, and soy proteins. A flexographic printing system is generally a system with a rubber or photopolymer plate, a reverse angle doctor blade, and a ceramic anilox roller on a central impression cylinder press. Flexographic presses can be used to print on substrate materials such as paper, plastic films, and the like. Flexographic printing is typically less expensive than lithographic printing because flexographic printing systems can use water-soluble or water-based ink compositions that are less expensive than oil-based ink compositions.

[0028] Some non-limiting examples of coatings exemplified as paints are provided herein. Paints typically contain four basic components: pigments, binders, liquors, and additives. Any or all of these components may be single components or may include multiple items. Pigments provide color and opacity to paints, and pigments are usually inorganic or organic in origin, with some pigments being synthetically manufactured. "Primary" pigments provide color and opacity (opaque coverage). A common primary pigment is titanium dioxide, which is white and is used in latex and oil-based paints. Specialty or extender pigments may also be used. Extenders are often selected to affect properties such as mattness, scrub resistance, stain resistance, and chalking resistance. Alum or clay may be used for this purpose. These pigments are added to paints to provide specific properties such as thickness, a certain gloss level (matt), and durability.

[0029] The binder holds the pigment and adheres it to the substrate surface, and the binder composition can have two or more components. In latex paint, the latex resin is the binder. For example, in latex paint, the binder can be 100% acrylic, vinyl acrylic (polyvinyl acetate), or styrenated acrylic. The pigment particles can be insoluble or simply form a suspension in the binder. The binder "bonds" the pigment into a tough, continuous film and helps the paint adhere to the surface as described above. In many embodiments, the binder starts out as a liquid in the formulation before drying or crosslinking into a film.

[0030] The liquor carries the pigment and binder and is the evaporating portion of a paint or coating product. The role of the liquor is to keep the paint in a fluid form for ease of application. Once applied to a surface, the liquor evaporates leaving a uniform film that then dries to form a protective coating. The liquor used is determined primarily by the solubility of the binder. In oil-based and alkyd paints, the liquor is typically a paint thinner, and in latex paints, the liquor is typically water.

[0031] Additives are ingredients used in low concentrations to provide specific properties, such as, but not limited to, mildew resistance, better flow and leveling, and anti-splatter properties. Common additives used in conventional paint formulations include rheology modifiers, surfactants, defoamers, coalescents, and biocides. Many other additives are well known in the art and may be utilized as needed to formulate a paint with desired properties.

[0032] Non-limiting examples of coatings exemplified as clearcoats are provided herein. Clearcoat is used broadly herein to refer to a transparent coating that forms an outer interface with the environment. For this reason, a clearcoat must be durable enough to withstand abrasion and chemically stable enough to withstand UV light. Clearcoats can be either solvent or water-based. In particular, to improve the weatherability of the clear finish provided by the clearcoat composition, a UV light stabilizer or combination of UV light stabilizers can be added to the topcoat composition in an amount of about 0.1-10% by weight based on the total weight of the binder. Such stabilizers include UV light absorbers, screeners, quenchers, and certain hindered amine light stabilizers. Antioxidants can also be added at about 0.1-5% by weight based on the total weight of the binder. Typical UV light stabilizers that are useful include benzophenones, triazoles, triazines, benzoates, hindered amines, and mixtures thereof. Micronized polymers as matting agents.

[0033] As initially described above, and compared to using entirely conventional silica as the matting agent in the above coatings, the present disclosure replaces some or all of the silica with a micronized polymer as the matting agent. As used herein, micronization refers to the process of reducing the average diameter of the particles of a solid material. Techniques for micronization focus on mechanical means such as milling and grinding. Micronization may also be achieved using spray micronization. The present disclosure is not intended to be limited by a particular technique of micronization, and thus any known technique may be used. The term micronization generally refers to reducing the average particle diameter to the micron range. In particular, various polymers may be micronized, such as high density polyethylene, low density polyethylene, polyethylene oxide, polytetrafluoroethylene, polypropylene, maleated polypropylene, and Fischer-Tropsch processed polymers.

[0034] The micronized polymer may have an average diameter ranging from about 6 microns to about 30 microns, for example, from about 10 microns to about 25 microns, or from about 14 microns to about 18 microns, in a preferred embodiment. Commercially available micronized polymers are available in the ACumist® line of products by Honeywell International Inc., New Jersey, USA. Thus, one differentiating factor between conventional silica and micronized polymers is the aforementioned average diameter, with conventional silica particle sizes typically being less than about 10 microns. It has been observed that when using any larger silica particles, even as-applied (dried, cured) films of about 50 microns or more, the silica particles may become visible in the coated film, whereas the micronized polymer does not present such concerns. Furthermore, silica particles have a tendency to "stack", so that particle size may double in the as-applied film, causing similar appearance problems. Furthermore, whereas silica particles that cause surface fractures in as-applied films to achieve matte finish are vulnerable to "overexposure" and would result in shearing under burnishing conditions, the micronized polymers of the present disclosure instead result in a reduction in the coefficient of friction of the as-applied film, which prevents abrasion and burnishing.

[0035] The loading of the micronized polymer in the coating composition (by weight of the coating composition) may generally be about 0.5% to about 15%, such as about 1% to about 12% or about 1.5% to about 10%. Thus, specific loading ranges may include about 0.5% to about 2%, or about 2% to about 5%, or about 5% to about 8%, or about 8% to about 12%, or about 12% to about 15%. An exemplary loading is about 5%, for example, about 4% to about 6%. The loading of the micronized polymer used in a particular coating composition may depend on the type and use of the coating composition, as well as the desired gloss reduction and desired material properties of the applied coating composition. Silica as a matting agent

[0036] According to some embodiments of the present disclosure, silica is only partially replaced by finely divided polymer as a matting agent, while in other embodiments, silica is completely replaced. Thus, some, but not all, embodiments include an amount of silica. Thus, silica is described herein. In general, the silica used to make the matting agent can be any silica prepared by gel process or precipitation process. In some embodiments, natural silica such as diatomaceous earth and crystalline silica can also be used.

[0037] The loading of silica in the above coating compositions (by weight of the coating composition) may generally be from about 0.5% to about 15%, such as from about 1% to about 12%, or from about 1.5% to about 10%, or from about 2% to about 6%. Thus, specific loading ranges may include from about 0.5% to about 2%, or from about 2% to about 5%, or from about 5% to about 8%, or from about 8% to about 12%, or from about 12% to about 15%. The loading of silica used in a particular coating composition may depend on the type and use of the coating composition, as well as the gloss reduction and material properties of the coating composition being applied.

[0038] Within the above ranges of micronized polymer and silica, when used in combination, the weight ratio of micronized polymer to silica may range from about 1:10 to about 10:1, such as from about 1:5 to about 5:1, such as from about 1:2 to about 2:1. Particular ranges of ratios may be from about 1:10 to about 1:5, or from about 1:5 to about 1:1, or from about 1:1 to about 5:1, or from about 5:1 to about 10:1. Of course, in embodiments where the silica is completely replaced by the micronized polymer, such ratios do not exist. The loading ratio between the micronized polymer and silica used in a particular coating composition may depend on the type and use of the coating composition, as well as the gloss reduction and material properties of the coating composition to be applied. Illustrative Examples

[0039] The present disclosure will now be illustrated by the following non-limiting examples. It should be noted that various changes and modifications can be applied to the following examples and processes without departing from the scope of the present disclosure defined in the appended claims. Therefore, it should be noted that the following examples should be interpreted as merely illustrative and not limiting in any way.

[0040] 1A and 1B are graphs showing the results of burnishing tests of water-based acrylic clearcoat compositions, where gloss was measured at 60 degrees in FIG. 1A and 85 degrees in FIG. 1B. Each example was loaded with 2% by weight of matting agent, ranging from pure silica on the left side of the graph to pure micronized polymer on the right side of the graph, with intermediate silica to micronized polymer ratios of 90:10, 80:20, and 70:30. The experiment was performed using a Sutherland abrasion tester, where each coating was rubbed 200 times with a 4 pound weight. The substrate was a Leneta Drawdown card, and the abrasion surface was either typing paper or a Leneta card. As shown, the only poor performers in burnish resistance (i.e., those that showed a significant increase in gloss) were the pure silica examples, while any inclusion up to the total micronized polymer substantially prevented any increase in gloss. Thus, the experiments shown in Figures 1A and 1B demonstrate the beneficial properties of using finely divided polymer in place of silica to prevent vanishing according to embodiments of the present disclosure.

[0041] Figures 2A and 2B show similar results at 6% total loading of matting agent (100% silica, and ratios of silica to micronized polymer of 90:10 and 80:20 were tested and shown).

[0042] 3A and 3B are photographs from an experiment to show the abrasion resistance of an embodiment of the present disclosure using 2% and 6% matting agent loadings, respectively. On the left side, the matting agent was pure silica, while on the right side, it was a 90:10 ratio of silica to micronized polymer. In both figures, significantly more abrasion is observed on the left side compared to the right side.

[0043] 4A-4D are graphs showing the various viscosities of various coatings when a matting agent is added. With respect to FIG. 4A, which represents a clear acrylic water-based wood coating, the leftmost bar is the control (no matting agent added), the next three bars from left to right contain 5% loadings of various silica matting agents, and the last eight rightmost bars contain 5% loadings of various micronized polymeric matting agents. FIG. 4B-4D are constructed in a similar manner, with FIG. 4B representing an architectural coating, FIG. 4C representing an epoxy coating, and FIG. 4D representing a solvent-based alkyd coating. As shown, the viscosity is much higher for the silica matting agents compared to the micronized polymeric matting agents across the entire range of coatings. This is believed to be due to the high oil absorption inherent to silica. Thus, FIG. 4A-4D show the benefit of lower viscosity according to embodiments of the present disclosure, which relates to the ease of application of the coating.

[0044] 5A-5D show that the burnishing results observed in the clearcoats of FIGS. 1A, 1B, 2A, and 2B are also observed in various other coatings. For example, the tests shown in the graph of FIG. 5A are based on offset paste inks rubbed with typing paper. The left group of bars is a control, the next two groups of bars on the right use various silicas, and the rightmost five groups of bars use various micronized polymers. Tests were performed with an 8% matting agent loading in FIG. 5A, and a 5% matting agent loading in FIG. 5B-5D, and burnish resistance was measured at gloss values ​​of 20, 60, and 85 degrees. FIGS. 5B-5D are constructed similarly to FIG. 5A and represent a clear water-based acrylic coating-satin finish (FIG. 5B), a two-component polyurethane coating-high gloss finish (FIG. 5C), and a water-based architectural coating-matte finish (FIG. 5D). As can be clearly seen, the minimal increased gloss value after 300 rubs of a 2 pound weight was the case utilizing micronized polymer as a matting agent. Furthermore, burnishing resistance is most effective at the 85° gloss level, which is the incident light and most noticeable to the human eye. Thus, the 85° gloss angle shows an initial high efficiency in reducing gloss using micronized polymer over silica, and thus micronized polymer shows better performance as a burnishing resist agent.

[0045] 6A-6E are graphs showing the results of matte efficiency testing for various coating compositions at 20, 60, and 85 degree gloss angles at 5% matte loading. FIG. 6A represents a clear water-based acrylic coating, satin finish. FIG. 6B represents a clear water-based acrylic coating, high gloss finish. FIG. 6C represents a water-based architectural coating, matte finish. FIG. 6D represents a solvent-based alkyd coating, high gloss finish, and FIG. 6E represents a two-component epoxy coating, high gloss. In each figure, the left group of bars is a control, the next 1-3 groups of bars on the right used various silicas, and the rightmost group of bars used various micronized polymers. As shown, the coatings using the micronized polymers of the present disclosure exhibited superior matte efficiency.

[0046] Further still, Figures 7A-7C illustrate the benefit of reduced color transfer in the context of paints and inks having a matting agent according to the present disclosure added. As shown in Figure 6A (paint) and Figure 6B (ink), after 300 rubs of a 2 pound weight, the control example on the left (no added micronized polymer) shows significantly more color transfer than the inventive example on the right, which included a 5 wt% loading of micronized polymer matting agent. Furthermore, Figure 6C shows the scrub resistance of an embodiment of the present disclosure.

[0047] Figures 8-11 show the effect of particle size differences on gloss reduction, burnish resistance, rub resistance, and viscosity increase. For example, Figure 8 is a graph showing gloss reduction by oxidized polyethylene micronized polymers of various particle sizes, particularly in the size range of 6 microns to 30 microns, when added to a water-based high gloss clear acrylic coating (85° gloss measurements after 5% polymer addition to a control coating with a starting 85° gloss of 91.9). Figure 9 is a graph showing burnish resistance by oxidized polyethylene micronized polymers of various particle sizes, particularly in the size range of 6 microns to 30 microns, when added to a solvent-based alkyd coating (85° gloss measurements after 5% polymer addition to a control coating and then burnishing with 80g A4 printing paper at 4 pounds for 200 cycles on a Sutherland 2000 rub resistance tester). Further, Figure 10 is a graph showing the abrasion resistance of oxidized polyethylene micronized polymers of various particle sizes, particularly in the size range of 6 microns to 30 microns, added to a solvent-based alkyd coating (after adding 5% polymer to a control coating and rubbing with 80g A4 print paper at 4 pounds for 200 cycles in a Sutherland 2000 abrasion resistance tester), and Figure 11 is a graph showing the viscosity increase of oxidized polyethylene micronized polymers of various particle sizes, particularly in the size range of 6 microns to 30 microns, added to a water-based architectural matte coating (after adding 5% polymer to a control coating and then measuring the viscosity difference vs. the control in a Brookfield viscometer).

[0048] Additionally, Figures 12A-15 show further test results for various polymer types with respect to gloss reduction, burnish resistance, rub resistance, and viscosity increase. For example, Figure 12A is a graph showing gloss reduction by oxidized polyethylene and polypropylene micronized polymers of various particle sizes, particularly in the size range of 14 microns to 18 microns, when added to a clear water-based acrylic coating (85° gloss measurements after 5% polymer addition to a control coating with an onset 85° gloss of 91.9). Figure 12B is a graph showing gloss reduction by oxidized polyethylene and polypropylene micronized polymers of various particle sizes, particularly in the size range of 14 microns to 18 microns, when added to a 2K polyurethane coating (85° gloss measurements after 5% polymer addition to a control coating with an onset 85° gloss of 97.9). Figure 13 is a graph showing the burnish resistance of polyethylene, polyethylene oxide, and polypropylene micronized polymers of various particle sizes, particularly in the size range of 14 microns to 18 microns, when added to a clear acrylic satin finish (85° gloss measurement after adding 5% polymer to a control coating and then rubbing with 80g A4 paper at 4 pounds for 200 cycles on a Sutherland 2000 rub resistance tester). Additionally, Figure 14 is a graph showing the rub resistance of polyethylene, polyethylene oxide, and polypropylene micronized polymers of various particle sizes, particularly in the size range of 14 microns to 18 microns, when added to an epoxy coating (after adding 5% polymer to a control coating and then rubbing with 80g A4 paper at 4 pounds for 200 cycles on a Sutherland 2000 rub resistance tester). Furthermore, FIG. 15 is a graph showing the viscosity increase of polyethylene, polyethylene oxidized, and polypropylene micronized polymers of various particle sizes, particularly in the size range of 14 microns to 18 microns, when added to an epoxy coating (after adding 5% of the polymer to a control coating and then measuring the viscosity difference versus the control with a Brookfield viscometer).

[0049] In general, advantages that may be observed with embodiments of the present disclosure include resistance to burnishing, good mar, abrasion, and scratch resistance, good surface slip and feel, minimal or no loss in matte efficiency of the coating while stored for extended periods of time, minimal or no settling during storage, low friability, low binder demand, low viscosity build-up, and the like, or excellent gloss reduction capabilities. Additionally, adverse effects that are generally avoided with embodiments of the present disclosure include burnishing, poor mar, abrasion, and scratch resistance, poor surface slip and feel, loss of matte efficiency over time, tendency to settle on storage, friability, high binder demand, and viscosity build-up.

[0050] Although at least one exemplary embodiment has been presented in the foregoing detailed description, it should be understood that a vast number of variations exist. It should also be understood that the exemplary embodiment(s) are merely examples and are not intended to limit the scope, applicability, or configuration of the present disclosure in any manner. Rather, the foregoing "Description of the Preferred Embodiments" will provide those skilled in the art with a convenient road map for implementing the exemplary embodiment(s). It should be understood that various changes can be made in the function and arrangement of elements without departing from the scope of the present disclosure, as set forth in the appended claims and their legal equivalents. This specification includes the disclosure of the following inventions. [Item 1] A matte finish coating for application to a substrate, comprising: A coating material; a finely divided polymeric matting agent; A matte finish coating, wherein the matte finish coating comprises the micronized polymeric matting agent in an amount of about 0.5% to about 15% by total weight of the matte finish coating. [Item 2] 2. The matte finish coating of claim 1, wherein the matte finish coating comprises the micronized polymeric matting agent in an amount of about 1.0% to about 12% of the total weight of the matte finish coating. [Item 3] 2. The matte finish coating of claim 1, wherein the coating material comprises an ink composition. [Item 4] 2. The matte finish coating of claim 1, wherein the finely divided polymeric matting agent comprises a high density polyethylene (HDPE) polymer or a low density polyethylene (LDPE) polymer. [Item 5] 2. The matte finish coating of claim 1, wherein the finely divided polymeric matting agent comprises polytetrafluoroethylene, polypropylene, maleated polypropylene, oxidized polyethylene, or a Fischer-Tropsch processed polymer. [Item 6] 2. The matte finish coating according to claim 1, wherein the finely divided polymer either completely replaces silica as a matting agent or alternatively further comprises a silica matting agent. [Item 7] 7. The matte finish coating of claim 6, wherein the weight ratio of the finely divided polymeric matting agent to the silica matting agent is from about 10:1 to about 1:10. [Item 8] Item 2. The matte finish coating of item 1, wherein the micronized polymer has an average particle diameter of about 6 microns to about 30 microns. [Item 9] 9. The matte finish coating of claim 8, wherein the micronized polymer has an average particle diameter of from about 10 microns to about 25 microns. [Item 10] 2. A substrate comprising the matte finish coating of item 1 coated on at least one surface thereof.

Claims

1. 1. A matte finish alkyd, epoxy or polyurethane coating for application to a substrate, comprising: A coating material; and a micronized polymeric matting agent comprising a micronized high density polyethylene (HDPE) polymer or a micronized low density polyethylene (LDPE) polymer, the HDPE or LDPE having an average particle diameter of 6 microns to 30 microns; said matte finish coating comprising said finely divided polymeric matting agent in an amount of 0.5% to 15% of the total weight of said matte finish coating and further comprising a silica matting agent; said matte finish coating comprising said micronized polymeric matting agent in an amount of 1.0% to 12% of the total weight of said matte finish coating; the weight ratio of the finely divided polymeric matting agent to the silica matting agent is from 10:1 to 1:10; and A matte finish alkyd, epoxy or polyurethane coating, wherein the coating material is selected from the group consisting of a clearcoat composition, a pigmented coating composition, a paint composition, and an ink composition.

2. 2. The matte finish alkyd, epoxy or polyurethane coating of claim 1, wherein the HDPE or LDPE has an average particle diameter of 10 microns to 30 microns.

Citation Information

Patent Citations

  • Paint for blackboard and like

    JP1978034833A

  • Matting agent for printing ink, printing ink composition comprising the same and its use

    JP2001089689A

  • Water and oil repelling woody building material

    JP2010005798A

  • Wood building material

    JP2010143153A

  • Low-fouling paint composition

    JP2016003250A